2014
DOI: 10.1063/1.4898799
|View full text |Cite
|
Sign up to set email alerts
|

Direct determination of the local Hamaker constant of inorganic surfaces based on scanning force microscopy

Abstract: The energetics involved in the bonding fluctuations between nanometer-sized silicon dioxide (SiO2) probes and highly oriented pyrolytic graphite (HOPG) and molybdenum disulfide (MoS2) could be quantified directly and locally on the submicron scale via a time-temperature superposition analysis of the lateral forces between scanning force microscopy silicon dioxide probes and inorganic sample surfaces. The so-called "intrinsic friction analysis" (IFA) provided direct access to the Hamaker constants for HOPG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…We assume that using diamond‐like carbon (DLC) tips instead of the mostly used silicon tips might cause the higher tip–sample attraction originating from a larger Hamaker constant of DLC compared to that of silicon oxide. [ 51 ] The short‐range flexural force ( F flex,3 ) shows a similar trend to that of the third‐eigenmode flexural frequency shift, although note a major difference in the region between the blue and orange dashed lines (tip–sample distance of 2–1.5 nm), where the short‐range flexural force shows a small attractive region. During approach, starting from the orange dashed line, the repulsive force increases initially with a very small gradient.…”
Section: Resultsmentioning
confidence: 83%
“…We assume that using diamond‐like carbon (DLC) tips instead of the mostly used silicon tips might cause the higher tip–sample attraction originating from a larger Hamaker constant of DLC compared to that of silicon oxide. [ 51 ] The short‐range flexural force ( F flex,3 ) shows a similar trend to that of the third‐eigenmode flexural frequency shift, although note a major difference in the region between the blue and orange dashed lines (tip–sample distance of 2–1.5 nm), where the short‐range flexural force shows a small attractive region. During approach, starting from the orange dashed line, the repulsive force increases initially with a very small gradient.…”
Section: Resultsmentioning
confidence: 83%
“…where 3 (¼78.5) is the relative dielectric constant of water, 3 0 (¼8.854 Â 10 À12 C V À1 m À1 ) is the permittivity of vacuum, R is the particle diameter, j 1 or j 2 is the surface potential, D is the separation distance, k is the inverse Debye length. 36 The energies of van der Waals interaction (W A ) can be calculated according to 37,38 W A ¼ ÀA 132 R/6D…”
Section: Dlvo Interactionsmentioning
confidence: 99%
“…Also, in previous investigation [13] of selfassembly process of CdS NC obtained by LB method on the surface of highly oriented pyrolytic graphite (HOPG) substrate we observed that during matrix annealing the NC tend to evenly cover HOPG surface. Hamaker constant of CdS-HOPG interaction equal to 17.86 10 -20 J [14] indicates predominance of the NC-substrate interaction. Both of the results show that at the low temperatures region selfassembly pattern mainly determined by van der Waals forces.…”
Section: Discussion Of Resultsmentioning
confidence: 99%